Analisis Kebutuhan Media BK Pada Remaja SMA dalam Mencegah Pelecehan Seksual Child Grooming - Wahid, Wahyu Kurniati; Latif, Suciani; Sinring, Abdullah (Universitas Palangka Raya, 2024)
This study aims to identify the needs of guidance and counseling (BK) media in preventing child grooming sexual harassment among high school students. The research method used was survey, with data collection techniques in the form of questionnaires and interviews in the form of Focus Group Discussion (FGD). The research subjects involved 81 randomly selected grade X students and the interview sessions were conducted with two counseling teachers and five students. Questionnaire data was analyzed descriptively to identify patterns of student needs, while interview data was analyzed using the thematic analysis method with the help of the NVivo application. The results showed that E-Book media and projects or simulations are highly needed by students, providing flexibility and practical experience in learning. In addition, interactive methods such as field trips and talk shows also received high appreciation from students. Thus, the use of interactive digital media such as E-Books in counseling services can effectively increase students' understanding and awareness regarding the prevention of sexual abuse cases such as child grooming.